2021
DOI: 10.15789/2220-7619-foa-1495
|View full text |Cite
|
Sign up to set email alerts
|

Features of antifungal therapy during long-lasting infectious process: a clinical case of fungal keratitis and profile of antifungal sensitivity based on assessing biofilm formation

Abstract: Among infectious diseases, opportunistic mycoses hold a special place. There has been accumulating a lot of evidence regarding the clinical and epidemiological aspects of infection caused by Fusarium spp., which global incidence rate among microbial keratitis ranges from 2 to 40% depending on the geographical location of the country. Colonizing mucous membranes, fungi can exist not only in the form of plankton, but form biofilms after surface attachment, which leads to elevated resistance to multiple antifunga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Using C. albicans as an example, it has been shown that biofilm forms inhibit the release of neutrophil extracellular traps and resist neutrophil attack [ 51 ]. The studies have proved that biofilms increase minimum inhibitory concentration (MIC) of antifungal medications (sometimes MIC exceeds those for plankton forms by 100 times and more) and play the role in resistance formation [ 45 , 52 ]. Antimycotics capable of affecting the biofilms are few and all of them induce formation of reactive oxygen species (ROS) [ 50 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Using C. albicans as an example, it has been shown that biofilm forms inhibit the release of neutrophil extracellular traps and resist neutrophil attack [ 51 ]. The studies have proved that biofilms increase minimum inhibitory concentration (MIC) of antifungal medications (sometimes MIC exceeds those for plankton forms by 100 times and more) and play the role in resistance formation [ 45 , 52 ]. Antimycotics capable of affecting the biofilms are few and all of them induce formation of reactive oxygen species (ROS) [ 50 ].…”
Section: Pathogenesismentioning
confidence: 99%